Resistance training in the heat improves strength in professional rugby athletes. Issue 3 (3rd July 2019) - Miles, Cory; Mayo, Brad; Beaven, C. Martyn; McMaster, Daniel T.; Sims, Stacy T.; Hébert-Losier, Kim; Driller, Matthew
ABSTRACT: Background: Muscle adaptations are potentially enhanced through resistance training in elevated environmental temperatures (>30°C) due to upregulated anabolic hormonal responses. Method: Eighteen professional rugby union athletes performed a 3-week resistance training intervention where they were randomly allocated into 2 groups: HEAT ( n = 8) with all lower-body training sessions performed in an environmental chamber set at 35°C and 37% relative humidity, or CON ( n = 10) where identical training was performed under temperate conditions (21°C and 45%). Pre- and post-training tests included measures of strength, power, endurance, speed and body mass. Results: Small effect sizes were found in favour of HEAT for the back squat ( g = 0.25) and bench press strength ( g = 0.22). All other measures were associated with trivial or unclear effects. A significant group × time interaction was found for body mass, associated with a trivial effect size ( g = 0.18, HEAT +1.5 kg; CON −0.8 kg). Discussion: Lower body resistance training in the heat led to small improvements in lower and upper body strength compared to the identical training program performed in temperate conditions. This observation is suggestive of a priming or potentiating effect of prior training in the heat.